ANALISIS METODE CASING WHILE DRILLING UNTUK SETTING CASING 16” PADA SUMUR C2 - Bobby Rifki Saputra; Asri Nugrahanti; Rizki Akbar (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2018)
C2 well is an exploration well located in south sumatera area managed by PT. MEPI in planned CSS field will be drilled to a depth of 12.000 ftTVD vertically. Planning the use of casing while drilling is done by using 16" protective casing on the trajectory 17-1/2" from a depth of 1.500 ft to 4.600 ft. The use of casing while drilling (CWD), is expected by using the casing as drillstring, then the clearance between the boreholes wall with the OD casing becomes small which will cause the event "Plastering Effect". This phenomenon is expected to isolate the wall of the drill hole which is easy to happen lost circulation. On vertical wells only need a casing method while drilling level-2 (non-retrievable) because at level-2 only casing with bits (drillshoe) only, where drillshoe will be left in the shoe casing. From the analysis results can be said on well C2 can be applied casing method while drilling because in terms of hydraulics drilling which the drill hole clearance with horsepower square inch method (HSI) and cutting lift based on cutting carrying index (CCI) is good, but for mechanics drilling needs to be considered torque, drag, and buckling loads. In terms of torque loads MLT Rings should be installed for 16” protective casing, from drag loads where the 2.000 HP rig can withstand maximum load of hookload, and 16" protective casing might not occur buckling as the maximum weight on bit (WOB) is still under critical buckling load.